1995
DOI: 10.1063/1.114287
|View full text |Cite
|
Sign up to set email alerts
|

Real time spectroscopic ellipsometry study of hydrogenated amorphous silicon p-i-n solar cells: Characterization of microstructural evolution and optical gaps

Abstract: Spectroscopic ellipsometry measurements have been performed during the preparation of hydrogenated amorphous silicon p-i-n solar cells in the SnO2:F/p-i-n/Cr configuration. Postdeposition data analysis yields the evolution of bulk, surface roughness, and interface layer thicknesses with ∼0.2 Å sensitivity. In addition, the dielectric functions and optical gaps of the p-, i-, and n-layers are determined in the analysis. With the real time measurement approach, the layer properties are determined in the actual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…An apparent mathematical relationship between the two sets of value cannot be found. This is different from the report of Koh et al [20] in 1996, where an obvious linear relationship is observed in amorphous Si C 1− :H thin film. It could be ascribed to the different testing material.…”
Section: Optical Property Analysis Spectroscopic Ellipsometer (Se)contrasting
confidence: 56%
“…An apparent mathematical relationship between the two sets of value cannot be found. This is different from the report of Koh et al [20] in 1996, where an obvious linear relationship is observed in amorphous Si C 1− :H thin film. It could be ascribed to the different testing material.…”
Section: Optical Property Analysis Spectroscopic Ellipsometer (Se)contrasting
confidence: 56%
“…Drévillon and co-workers 34,35 and Collins and co-workers 5,[34][35][36][37][38] have examined a-Si:H grown on a variety of substrates. 5,[36][37][38][39][40] We compare our results with those for the silicon substrates with the native oxide, which should most closely resemble our surface. To validate the complex modeling of the spectroscopy data, Lu et al have performed …”
Section: Ellipsometry Measurements Of A-si:hmentioning
confidence: 92%
“…39,40 They report a linear relationship d s ϭ1.4d rms ͑AFM͒ϩ0.4 nm between the two methods of measuring the roughness.…”
Section: Fig 7 Dynamic Scaling Model For the Behavior Of G(rt)mentioning
confidence: 99%
“…However, it is known that the effective thickness is virtually identical for both cases from the results of the real time spectroscopic ellipsometry ͑RTSE͒ measurement. 7 In Figs. 1 and 2, although the p-layer thickness was identical, the V oc and fill factor of the cells with hydrogen treatment were higher than those without hydrogen treatment except for the case of 90 s p-layer deposition time which is the case of very thin p-layer thickness.…”
Section: ͓S0003-6951͑97͒02039-1͔mentioning
confidence: 95%